Control of the intensity of effort. heart rate or rate of perceived effort - Rui Canário-Lemos; Victor Machado-Reis; Nuno Garrido; Tiago Rafael-Moreira; Rafael Peixoto; Bruno Nobre-Pinheiro; Gabriela Monteiro; José Vilaça-Alves (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: the goal of the present study was to compare the oxygen uptake between three experimental sessions of the Air Bike PRO® class, which the difference between sessions was the method used to control intensity of effort: SL) external load corresponds to ventilatory thresholds and 90% peak VO2; SRPE) rate perceived effort; SHR) heart rate. Methods: Ten physically active young men aged between 21 and 30 years old (mean ± standard deviation: 25.4 ± 4.81) participated in 3 study sessions, where they performed 3 Air Bike PRO® classes, in a randomized way. VO2 was measured in all sessions during the Air Bike PRO® class. Results: The values ​​of absolute VO2 (l/min) were significantly higher in the SL compared to the SHR in the 20 to 30 minute block and in music tracks 5 and 8 (p<0.05). Relative VO2 (ml / Kg / min) was significantly higher in the SL compared to the SHR in the 10 to 20 minute and 20 to 30 minute block and in music tracks 5, 6, 7, 8 and 9 (p<0.05). In the SRPE, significantly higher values ​​were also observed compared to the SHR, in the 20 to 30 minute block and in music tracks 5 and 8 (p<0.05). Conclusion: According to the data of the present study, it is possible to conclude that the SRPE presents more similarities with the SL.